Income and the CARD Act's ability-to-pay rule in the US credit card market - Scott L. Fulford; Joanna Stavins (Federal Reserve Bank of Boston, 2024)
In consumer credit, "ability-to-pay" (ATP) rules require lenders to consider whether the consumer can repay a loan without experiencing undue hardship. ATP rules have recently been implemented or considered in many countries and markets. Using a large panel of credit card accounts, we study the 2009 Credit Card Accountability Responsibility and Disclosure (CARD) Act's ATP rule and its effect, if any, on the US credit card market. We find that the rule appears to have had no effect on bank credit decisions because actual credit limits are almost always substantially lower than reasonable ATP limits. We examine other factors that may explain banks' credit decisions. Nearly 27 percent of consumer accounts that had a change in cardholder income received a credit limit increase of 100 or more in the same month as the income change. Most credit limit increases followed an income increase, although 19 percent of the instances of an income decrease also were followed by a credit limit increase. Most credit limit increases occurred without cardholders providing banks with income updates. The magnitude of the income change coefficient when an income update occurred is estimated to be nearly zero. We conclude that after the origination of an account, the direction and size of the account holder's income updates are largely unimportant for credit limit changes from either a regulatory or bank profitability standpoint.
Keywords: G21; G51; D14; E42; 330; ability to pay; CARD Act; credit cards; credit limits